Peningkatan Proses Pembelajaran Tematik Terpadu Tema2 Sub Tema 3 menggunakan Pendekatan Saintifik Di Kelas V SDN 11 Tanjung Alai Kota Lubuk Sikaping - Riandi, Taufik (Universitas Negeri Padang, 2022)
This research is motivated by the phenomenon of the number of students looking less active in questioning, reasoning, teacher-centered learning, students seem not so enthusiastic in communicating the results of their work The scientific approach in integrated thematic learning has not been maximally implemented. This study aims to describe the improvement of the integrated thematic learning process by using a scientific approach in theme 2 in class V SDN 11 Tanjung Alai, Lubuk Sikaping City. This research is a classroom action research with qualitative and quantitative approaches. The subjects of this study were grade V students of SDN 11 Tanjung Alai Lubuk Sikaping who were registered in the 2018/2019 academic year with 22 students consisting of 10 male students and 12 female students. The research design consisted of planning, implementing, observing, and reflecting. The results revealed that the integrated thematic learning process using the Scientific Approach model in class V SDN 11 Tanjung Alai Lubuk Sikaping, Pasaman Regency, obtained an increase in the learning process. This can be seen from the aspect of the teacher in the first cycle of meeting 1 getting 69.64% with sufficient qualifications and 76.79% at meeting 2 with good qualifications, while in the student aspect meeting 1 obtained 69.23% with sufficient qualifications and 75% in meeting 2 with Good qualifications. Whereas in cycle 2 the assessment from the teacher aspect increased to 96.43% with Very Good qualifications, 96.15% with Very Good qualifications in the student aspect.